Joining process and strength in PVC friction stir spot welding with fabricating composite material at welding area*. Issue 5 (4th May 2017) - Kurabe, Yohei; Miyashita, Yukio; Hori, Hisashi
Abstract: In order to improve the strength of FSSWed PVC joints, SiC particles were compounded into the welded region at the same time as the welding process. The joining process and its effect on strength of FSSWed PVC joints were investigated in a joining experiment with a PVC plate having a different guide hole diameter for filling the SiC particles. In the case of the specimen compounded with SiC particles with guide hole diameter of 8 mm, SiC particles could be dispersed uniformly in the welded area. In the specimens with guide hole diameters of 5 and 2 mm, dispersion of SiC particles was not observed inside of the welded area. Degradation and increase in local mechanical property was significantly observed at edge of the keyhole and inside the welded area, respectively, in the specimen with a guide hole diameter of 8 mm. The width of welded area increased with increasing guide hole diameter. The joining strength was improved by fabricating composite material in the welded region. The strength increased with increasing guide hole diameter. It is considered that joining strength was significantly affected by the width of the welded area. According to temperature distribution and observation of material flow using a high speed camera, contact between the welding tool and SiC particles before plunging into a lower sheet induced increasing heat input during the process and resulted in promoting the friction stirring. Therefore, it is considered that change in guide hole diameter leads to change in contact area between welding tool and SiC particles and also change in width of the welding area resulting in change in the joining strength.